2000
DOI: 10.1038/35046566
|View full text |Cite
|
Sign up to set email alerts
|

A novel mitochondrial septin-like protein, ARTS, mediates apoptosis dependent on its P-loop motif

Abstract: Here we describe a protein product of the human septin H5/PNUTL2/CDCrel2b gene, which we call ARTS (for apoptosis-related protein in the TGF-beta signalling pathway). ARTS is expressed in many cells and acts to enhance cell death induced by TGF-beta or, to a lesser extent, by other apoptotic agents. Unlike related septin gene products, ARTS is localized to mitochondria and translocates to the nucleus when apoptosis occurs. Mutation of the P-loop of ARTS abrogates its competence to activate caspase 3 and to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
232
1
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(246 citation statements)
references
References 37 publications
3
232
1
6
Order By: Relevance
“…The signature motifs (G-boxes) of the GTPase superfamily are present in all septin family members except ARTS, a splice variant of Sept4 that lacks the G4 box [56]. Many septins bind and hydrolyze GTP [7,28,45,55].…”
Section: Regulation Of Septin Polymerizationmentioning
confidence: 99%
“…The signature motifs (G-boxes) of the GTPase superfamily are present in all septin family members except ARTS, a splice variant of Sept4 that lacks the G4 box [56]. Many septins bind and hydrolyze GTP [7,28,45,55].…”
Section: Regulation Of Septin Polymerizationmentioning
confidence: 99%
“…The upstream activator of TAK1, TAB1 (Shibuya et al, 1996), may be linked to receptor activation via HPK1 or Xlinked inhibitor of apoptosis (XIAP) in case of TGF-b or BMP, respectively (Wang et al, 1997;Yamaguchi et al, 1999). Recently, ARTS, apoptosis-related protein in the TGF-b signaling pathway (Larisch et al, 2000), a protein belonging to the septin family, was found to enhance cell death by TGF-b. ARTS is localized to mitochondria and translocates to nucleus when apoptosis occurs (Fig.…”
Section: Regulation Of Apoptosis By Smadsmentioning
confidence: 99%
“…potentiates transforming growth factor-b/Smad2 pathway Transforming growth factor-b is a potent inducer of growth inhibition and apoptosis of NRP-154 cells (Larisch-Bloch et al, 2000). Using retroviral cDNA expression libraries, we identified an antisense transcript of ELAC2 as a possible mediator for conferring a TGFb resistant phenotype to NRP-154 prostate cells.…”
Section: Elac2mentioning
confidence: 99%